Overlooked Opportunity: Tradable Business Services, Developing Asia, and Growth - J. Bradford Jensen (Asian Development Bank (ADB), 2013)
This paper argues that developing Asia is overlooking an opportunity for increased growth and development through trade in business services. Developing Asia would benefit from liberalizing services trade as it has benefited from liberalizing goods trade. This argument rests on these key findings: business services are important for growth, developing Asia is relatively under- endowed with business services, many business services are tradable, and developing Asia has relatively high barriers to services trade.
hdl:11540/2086
Keywords: F13; F14; F63; 330; services; trade barriers; Asia; Dienstleistungshandel; Handelshemmnisse; Handelsliberalisierung; Wirtschaftswachstum; Asien